Reimagining Islamic Microfinance in the Age of AI:A Qualitative Exploration of Human-Centric Sharia Banking - Marini Marini; Dharma Setiawan (Indonesian Development Economics and Localities, 2025)
The rapid integration of artificial intelligence (AI) into global financial systems presents both transformative opportunities and profound ethical challenges for Islamic microfinance institutions. This study explores the intersection of AI-driven financial technologies and the foundational principles of Sharia-compliant banking, with particular emphasis on the preservation of human-centric values embedded in Islamic economic thought. Drawing on qualitative data gathered through in-depth interviews with Islamic microfinance practitioners, Sharia scholars, financial technology experts, and end-users in Indonesia, this research employs thematic analysis to identify critical tensions and synergies between algorithmic efficiency and the ethical imperatives of maqasid al-Shariah. Four principal themes emerge from the analysis: (1) the efficiency–humanity tension in AI deployment; (2) ethical concerns surrounding algorithmic bias and data privacy; (3) the dynamics of customer trust in digitised Islamic finance; and (4) the challenges of maintaining Sharia compliance within automated systems. The findings suggest that while AI holds considerable promise for enhancing financial inclusion and operational efficiency, its uncritical adoption risks eroding the relational, compassionate, and justice-oriented ethos that distinguishes Islamic microfinance. This article argues for a deliberate, values-driven framework that positions human welfare at the centre of any technological transition in Sharia banking.